2015
DOI: 10.1016/j.ssi.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The “filler effect”: A study of solid oxide fillers with β-Li3PS4 for lithium conducting electrolytes

Abstract: Solid electrolytes are the subject of intense study partly because of their use in safer, high energy density, all-solid-state lithium-ion batteries. The addition of solid oxide fillers has been previously explored as a way to increase the ionic conductivity in composite electrolytes; however, no comparative study of the effect of both ion-conducting and non-conducting oxides on solid lithium superionic conductor electrolyte is reported. Nano-crystalline β-Li 3 PS 4 (LPS) was recently shown to have anomalous h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…At lower concentration of oxides, the ionic conductivity is increased by the change of charge carrier distribution in the composite caused by the surface acidity of oxides. With a high concentration of oxides in the system, the oxides particles block the motion of Li ions (Figure d) . Similarly, Rangasamy et al studied the composite of Li 7 La 3 Zr 2 O 12 (LLZO, conductivity 4 × 10 −4 S cm −1 at room temperature) and β‐Li 3 PS 4 .…”
Section: Sulfide‐based Solid‐state Electrolytesmentioning
confidence: 94%
See 1 more Smart Citation
“…At lower concentration of oxides, the ionic conductivity is increased by the change of charge carrier distribution in the composite caused by the surface acidity of oxides. With a high concentration of oxides in the system, the oxides particles block the motion of Li ions (Figure d) . Similarly, Rangasamy et al studied the composite of Li 7 La 3 Zr 2 O 12 (LLZO, conductivity 4 × 10 −4 S cm −1 at room temperature) and β‐Li 3 PS 4 .…”
Section: Sulfide‐based Solid‐state Electrolytesmentioning
confidence: 94%
“…“A” represents the addition of no oxide filler, “B” represents the space‐charge effect, and “C” shows the blocking effect of the oxide filler. Reproduced with permission . Copyright 2015, Elsevier.…”
Section: Sulfide‐based Solid‐state Electrolytesmentioning
confidence: 99%
“…1c. For the combination of an oxide SE with a thiophosphate one-Li 7 La 3 Zr 2 O 12 (LLZO) and β-Li 3 PS 4 (LPS) for example-the processing temperature can be reduced compared to the pure oxide and the ionic conductivity is enhanced because of space-charge effects at the interface [35,36]. SE fillers are also commonly used in polymer matrices [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Even less focus was put on the interfacial properties between two different SEs in batteries [8,35,36]. Only resistances and activation energy were reported, as well as X-ray diffraction (XRD) data to show the absence of decomposition of the bulk materials [35,36]. To gain knowledge about the actual contribution of the interfacial transport between both SEs, a model system is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, at most, the addition of 10% TiO 2 could raise the RT ionic conductivity of 85PEG–15Mg(NO 3 ) 2 to 10 −4 S cm −1 . [50a] Liang and co‐workers compared the effects of ion‐conducting fillers (Li 6 ZnNb 4 O 14 (LZNO)) and nonconducting fillers (Al 2 O 3 , SiO 2 ) on Li + mobility in β‐Li 3 PS 4 (LPS) solid‐state electrolyte . For the 10:90 (LZNO:LPS) composite, the ionic conductivity reached 2.44 × 10 −4 S cm −1 and was the highest among the three LPS–filler composites, indicating the unique interface effect between the LZNO and LPS.…”
Section: Progress Of Borohydride‐based Solid‐state Electrolytes and Amentioning
confidence: 99%